Financial Crime, ICT & E-Governance: Libraries Role - Olowu, Kemi; Gabasa, P. (Advances in Social Sciences Research Journal, 2020)
Love of money is the root of all evil (I Tim. 6:10) More than thirty financial crime are listed in this work making it like a spaghetti bowl. The list is inexhaustive with aid of ICT which is simply “putting old wine in new bottles” Elements of financial crime, consequences of these on the society and leeway for escape from justice in this climate are listed. From clumsy adjudication, corruption in judiciary, in availability of experts ,nonexistence of e-governance, dead forensic laboratories to empower Questioned Documents Examination (QDE), dearth of criminal profiling, jurisdictional discrepancies due to extra territoriality of the crime, short lifespan of cyber storage devices and double standards of investigatory unit, to difficulty of physical presence of suspects of borderless crimes. Overcoming these impediments are herculean but attainable. Recommendations to stem these crime’s negative effects on the economy and distortion of social stability etc. range from punishments bothering on cruelty and inhumanity like South Korea’s death penalty, documentation of financial criminals globally and information dissemination on such. Treaties on such crimes should be published widely, resuscitation of forensic laboratories to empower analysis of disputed signatures, fingerprints of ex-convicts.(CCR), Cross fertilization of ideas by jurists in foreign lands and reports in law libraries. Possibilities in virtual environments via ICT are listed such as “FinTrack” software etc. to stem this unethical public, financial behaviour.